In Vitro Propagation and Biochemistry of Rosa Hybrida L. cv. ‘First Red’ and Clonal Fidelity of Microplants - Kaur, Amanpreet (My University, 2013)
In vitro propagation of rose has played a very important role in rapid multiplication of cultivars with desirable traits and production of healthy and disease-free plants. Shoot multiplication of Rosa hybrida cv. ‘First Red’ was initiated by supplying BAP and GA3 to obtain wide number of shoots. BAP and GA3 were found to be most effective growth hormones for shoot multiplication. To induce shoot organogenesis leaf explants were inoculated on different concentrations of auxins and cytokinins. Among the different auxins and cytokinins studied and over all explant types, (BAP- 12.5 µM and NAA- 25 µM; BAP- 25 µM and 2, 4-D – 12.5 µM) promoted the highest frequency of callus production for shoot regeneration. But unfortunately no shoot regeneration was obtained. Rooting was obtained on 50 µM IBA concentration for a short exposure of 12 hrs. Among biochemical parameters, carbohydrates, phenols and amino acids were found in the sequence of first increasing and then gradually decreasing following IBA treatment. The content of carbohydrates were seemed to be increasing from the 1st day of inoculation after IBA pulse treatment and then decreased as the root started emerging. Therefore, interpretation can be made that carbohydrates, phenols and amino acids may be involved in adventitious root growth. Random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) analyses indicated clonal uniformity of the newly formed in vitro raised plants, and these were also found to be true-to-type.
M.Sc. (Biotechnology)
Keywords: Micropropagation; Carbohydrates; Rooting